2023
DOI: 10.1111/exsy.13444
|View full text |Cite
|
Sign up to set email alerts
|

A military reconnaissance network for small‐scale open‐scene camouflaged people detection

Maozhen Liu

Abstract: Although the work of identifying animal and plant objects with highly similar patterns (e.g., texture, intensity, colour, etc.) to the background has recently attracted more research interest but rarely involves the military complex environment. Design an efficient camouflage small‐scale object detection algorithm that is capable of quickly discriminating the objects in open scenes from a long distance, to pre‐empt the enemy. In this work, we first recognize the fact that existing open‐source training datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In this study we compared the performance of both humans and the pretrained YOLOv4-tiny model for the detection of camouflaged persons. Since YOLOv4 was introduced several newer versions have appeared that either prioritize balancing the tradeoff between speed and accuracy rather than focusing on accuracy [52,53] improve the accuracy of person detection in conditions with occlusion [54][55][56][57][58][59][60][61][62] or camouflage [63][64][65], or enhance the detection of camouflaged objects in general [66]. In contrast, the study reported here was performed to investigate if YOLO can predict human detection performance for camouflaged targets.…”
Section: Limitationsmentioning
confidence: 99%
“…In this study we compared the performance of both humans and the pretrained YOLOv4-tiny model for the detection of camouflaged persons. Since YOLOv4 was introduced several newer versions have appeared that either prioritize balancing the tradeoff between speed and accuracy rather than focusing on accuracy [52,53] improve the accuracy of person detection in conditions with occlusion [54][55][56][57][58][59][60][61][62] or camouflage [63][64][65], or enhance the detection of camouflaged objects in general [66]. In contrast, the study reported here was performed to investigate if YOLO can predict human detection performance for camouflaged targets.…”
Section: Limitationsmentioning
confidence: 99%